The relationship between total quality management practices and academic performance of primary school and teaching innovation as mediator in Abu Dhabi - Alhosani, Mohamed Salem Ahmed Ibrahim (2023)
This study investigates total quality management practices (TQM) and primary school academic performance (PSAP) in Abu Dhabi: Teaching innovation as a mediator using a quantitative research design. The study also aspired to determine the relationship between TQM and teaching innovation, dimensions of TQM and PSAP, dimensions of teaching innovation and PSAP, and mediating role of teaching innovation on relationship between TQM and PSAP. A total of 342 teachers were chosen as a sample through quota and simple sampling. Data analysis using structural equation modelling was used. The findings revealed a significant relationship between TQM practices and primary school academic performance with a coefficient of (=-0.88, p<0.001) and a significant relationship between TQM practices and teaching innovation with a value of (=0.93, p<0.001). The study further found a significant relationship between teaching innovation and primary school academic performance at (=1.05, p<0.001). It found that teaching innovation mediates the relationship between TQM practices and primary school academic performance where teaching innovation acts as a partial mediator where total indirect effect was (1.38) < direct effect (-0.50). As the findings confirmed that the TQM practices matters in determining primary school academic performance, it is a sine qua non for school principals and policy makers to equip teachers with adequate and sufficient teaching materials to implement school quality successfully. Also, as teaching innovation plays a critical role in governing the relationship between TQM practices and PSAP, in-depth focus on innovation is the most effective way to increase the likelihood of teachers to embrace quality of change in the school. In the future, this study of TQM practices can be used by schools in the Abu Dhabi region to improve primary schools academic performance. The study suggests that TQM should be internalised and used to improve primary school academic performance in Abu Dhabi. In conclusion, further investigations should examine the role the TQM plays on primary school academic performance.